2002
DOI: 10.1159/000048600
|View full text |Cite
|
Sign up to set email alerts
|

Frequency Distribution and Haplotypic Heterogeneity of β<sup>E</sup>-Globin Gene among Eight Minority Groups of Northeast Thailand

Abstract: The frequencies of hemoglobin E and βE-globin gene haplotypes were determined in eight minority groups living in the northeastern part of Thailand. A total of 478 samples of eight minority groups, namely Soui, Thai Khmer, So, Yor, Phuthai, Thai Puan, Thai Loei and Thai Dam, were examined. High prevalences of hemoglobin E (>50%) were observed in Soui, Thai Khmer, So, Yor and Phuthai inhabiting the region near Cambodia and Laos. Thai Puan, Thai Loei, Thai Dam and native Thai living in the same geograp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
39
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 65 publications
(46 citation statements)
references
References 13 publications
7
39
0
Order By: Relevance
“…The same haplotype has been reported in Chinese (Zhou et al 1995). Thus, HbE variants in the studied Thai population and Chinese may have the same origin (i.e., the HbE mutation may have occurred on a chromosome containing the (AT) 9 (T) 5 repeat and rapidly spread into Southeast Asia) although HbE variants with different origins are suggested to exist in Thailand (Fucharoen et al 2002). Assuming that the present relative allele frequencies of the (AT) x (T) y repeats on HbA chromosomes correspond to the frequencies of these repeats at the time of HbE mutation, (AT) 9 (T) 5 would have been one of the dominant alleles.…”
Section: Discussionsupporting
confidence: 67%
“…The same haplotype has been reported in Chinese (Zhou et al 1995). Thus, HbE variants in the studied Thai population and Chinese may have the same origin (i.e., the HbE mutation may have occurred on a chromosome containing the (AT) 9 (T) 5 repeat and rapidly spread into Southeast Asia) although HbE variants with different origins are suggested to exist in Thailand (Fucharoen et al 2002). Assuming that the present relative allele frequencies of the (AT) x (T) y repeats on HbA chromosomes correspond to the frequencies of these repeats at the time of HbE mutation, (AT) 9 (T) 5 would have been one of the dominant alleles.…”
Section: Discussionsupporting
confidence: 67%
“…Although extensive sequence analysis has not been carried out, from examination of the haplotypic backgrounds for E alleles in northeast Thailand, more than one mutational origin (Fucharoen et al, 2002) is suggested. However, the E allele found in China is on the same haplotype as that found in Thailand (Ohashi et al, 2005), suggesting that it does not have a different origin.…”
Section: E or B E Or Hbementioning
confidence: 99%
“…In this paper, we describe the molecular basis and phenotype-genotype correlation in patients with Hb H and AEBart’s diseases of northeast Thai descent with a high prevalence of Hb E [17]. Unlike other populations in which the Hb H disease is much more frequently due to deletions than nondeletion mutations [18, 19, 20, 21, 22, 23, 24], as shown in table 1, the Hb H disease in this group of the Thai population most commonly (35 of 52 cases, 67.3%) results from the combination of α-thalassemia 1 (SEA) and Hb CS (–– SEA /α CS α) and less commonly (14 of 52 cases, 26.9%) from the interaction of α-thalassemia 1 (SEA) and deletional α-thalassemia 2 (–– SEA /–α).…”
Section: Discussionmentioning
confidence: 99%